TETRACARPIDIUM CONOPHORUM EXTRACT EXHIBITS ANTI-FATIGUE ACTIVITY IN RATS VIA REDUCED PROTEIN CATABOLISM, INCREASED ANTIOXIDANT STATUS AND DELAYED LACTATE ELEVATION (FUDMA JOURNAL OF SCIENCES, 2021)
Thirty rats of both sexes were assigned into 5 categories of six animals apiece. Animals in the unadministered (control) group were placed on distilled water. Group 1M and Group 1F animals were administered 500 mg/kg body weight (b.w) of T. conophorum aqueous nut extract whereas animals in Group 2M and Group 2F were administered 750 mg/kg dosage of the extricate (0.5 ml) orally once daily for 32 days. Phytoconstituents present in the extract include: saponins, flavonoids, tannins, phenols and alkaloids. The extract at 750mg/kg b.w notably (p
Keywords: Fatigue; Tetracarpidium conophorum; Euphorbiaceae; Swim endurance time; Lactate